2018
DOI: 10.1007/s00405-018-05263-x
|View full text |Cite
|
Sign up to set email alerts
|

Staging and prognosis of oropharyngeal carcinoma according to the 8th Edition of the American Joint Committee on Cancer Staging Manual in human papillomavirus infection

Abstract: PurposeThe aim of this study was to evaluate the 8th edition of the American Joint Committee on Cancer Staging Manual: Head and Neck Section on oropharyngeal squamous cell cancer (OPSCC) and to clarify the relationship between p16 overexpression and the presence of human papillomavirus (HPV) DNA using fresh frozen samples.MethodsSamples from 100 OPSCC patients were analyzed using polymerase chain reaction (PCR) and p16 immunohistochemistry.ResultsFive-year overall survival (OS) was 73.0%, 93.9%, and 62.2% in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 23 publications
5
38
1
Order By: Relevance
“…Previous studies already indicated that different constellations of the p16-and HPV-status can define further prognostic divergent subgroups within OPSCCs [19][20][21][22][23][24]. Nevertheless, studies reporting long-term oncologic results of subgroups defined by p16-and HPV-status combined are rare [19][20][21][22][23][24], even though a meta-analysis by Albers et al included 24 studies that investigated the survival of patients with HNSCC and evaluated p16-and HPV-status [24]. A comparison of our study with this meta-analysis seems limited due to the following reasons: only 13 of the included studies selectively focused on OPSCCs, and only two of them provided the 5-year survival estimates of patients treated with curative intent, with no cases of distant metastases included [21,38].…”
Section: Survival Based On P16 and Hpv-status Combinedmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies already indicated that different constellations of the p16-and HPV-status can define further prognostic divergent subgroups within OPSCCs [19][20][21][22][23][24]. Nevertheless, studies reporting long-term oncologic results of subgroups defined by p16-and HPV-status combined are rare [19][20][21][22][23][24], even though a meta-analysis by Albers et al included 24 studies that investigated the survival of patients with HNSCC and evaluated p16-and HPV-status [24]. A comparison of our study with this meta-analysis seems limited due to the following reasons: only 13 of the included studies selectively focused on OPSCCs, and only two of them provided the 5-year survival estimates of patients treated with curative intent, with no cases of distant metastases included [21,38].…”
Section: Survival Based On P16 and Hpv-status Combinedmentioning
confidence: 99%
“…Therefore, it was previously used as a surrogate marker for identification of HPV-associated OPSCCs [17,18]. Nevertheless, previous studies suggest that the combination of both markers, p16-and HPV-status, define prognostic divergent subgroups [19][20][21][22][23][24]. This needs to be considered, especially since treatment de-intensification trials investigated altered therapeutic regimes for HPV-associated OPSCCs [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancer is the sixth most common cancer worldwide, accounting for approximately 5% of all cancer cases (12). Excessive alcohol consumption and smoking are well-known risk factors for head and neck cancer (13,14). Although alcohol and tobacco use have decreased in recent years, the incidence of oropharyngeal cancer has nevertheless continued to increase (15).…”
mentioning
confidence: 99%
“…The main cause of this phenomenon is the increase in the incidence of human papillomavirus (HPV)-related oropharyngeal cancer arising in the tonsillar region and the base of the tongue (16). HPV-related oropharyngeal squamous cell carcinoma (OPSCC) has a significantly better survival rate compared with other forms of OPSCC (14,17,18). The clinical staging system for OPSCC separates HPV-related cancer from HPV-unrelated cancer in the 8th edition American Joint Committee on Cancer (AJCC) TNM classification (18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation